Characteristics of Asphalt Mixed Using Mountain Stone - Eswan Eswan; Sakti A. Adisasmita; M. Isran Ramli; Syafruddin Rauf (Salehan Institute of Higher Education, 2021)
Aggregate is the main thing in asphalt mixtures with a percentage of about 70% to 80%. The aggregate used should meet the Indonesian National Standard (SNI) before being used in the asphalt mixture. East Kalimantan Province is one of the provinces in Indonesia which always brings in aggregates from outside the region for road construction. This study aims to analyze the modulus of stiffness of the AC-WC mixture using local aggregate of East Kalimantan Province and petroleum bitumen grade 60/70 as a binder due to water immersion. This research is experimental in the laboratory. The variation of the petroleum bitumen content used was 4.5, 5.0, 5.5, 6.0 and 6.5%. Water immersion was carried out at the age of 3, 5 and 7 days. The results showed that at 3 days of immersion, the resilient modulus values obtained at petroleum bitumen content of 4.5, 5.0, 5.5, 6.0 and 6.5% were 421.0, 506.0, 872.5, 747.0 and 648.5 MPa, respectively. At 5 days immersion, the resilient modulus values obtained were 383.5, 386.0, 915.5, 561.0 and 555.5 MPa, respectively. Whereas for the 7 days immersion, the resilient modulus were 290.5, 425.5, 1369.0, 547.5 and 525.0 MPa, respectively. It can be seen that water immersion greatly affects the stiffness modulus of the asphalt mixture. This stiffness will cause the asphalt mixture to be easily damaged or cracked. This can be caused by the influence of the sub-standard aggregates used, namely Senoni stone and Mahakam sand. Doi: 10.28991/cej-2021-03091652 Full Text: PDF